Hypercholesterolemia induced cerebral small vessel disease - Kraft, Peter; Schuhmann, Michael K.; Garz, Cornelia; Jandke, Solveig; Urlaub, Daniela; Mencl, Stine; Zernecke, Alma; Heinze, Hans-Jochen; Carare, Roxana O.; Kleinschnitz, Christoph; Schreiber, Stefanie (PLoS ONE, 2017)
Background: While hypercholesterolemia plays a causative role for the development of ischemic stroke in large vessels, its significance for cerebral small vessel disease (CSVD) remains unclear. We thus aimed to understand the detailed relationship between hypercholesterolemia and CSVD using the well described Ldlr-/- mouse model. Methods: We used Ldlr-/- mice (n = 16) and wild-type (WT) mice (n = 15) at the age of 6 and 12 months. Ldlr-/- mice develop high plasma cholesterol levels following a high fat diet. We analyzed cerebral capillaries and arterioles for intravascular erythrocyte accumulations, thrombotic vessel occlusions, blood-brain barrier (BBB) dysfunction and microbleeds. Results: We found a significant increase in the number of erythrocyte stases in 6 months old Ldlr-/- mice compared to all other groups (P < 0.05). Ldlr-/- animals aged 12 months showed the highest number of thrombotic occlusions while in WT animals hardly any occlusions could be observed (P < 0.001). Compared to WT mice, Ldlr-/- mice did not display significant gray matter BBB breakdown. Microhemorrhages were observed in one Ldlr-/- mouse that was 6 months old. Results did not differ when considering subcortical and cortical regions. Conclusions: In Ldlr-/- mice, hypercholesterolemia is related to a thrombotic CSVD phenotype, which is different from hypertension-related CSVD that associates with a hemorrhagic CSVD phenotype. Our data demonstrate a relationship between hypercholesterolemia and the development of CSVD. Ldlr-/- mice appear to be an adequate animal model for research into CSVD.
CRIS-Team Scopus Importer:2023-03-23